11 Hospice and palliative care for advanced cardiac diseases in hong kong. (24th April 2019) - Lo, Raymond SK
Abstract : Advanced cardiac diseases are common non-cancer conditions that require good palliative care. Palliative Care should embrace both cancer and non-cancer conditions, and is applicable early in the course of illness, in conjunction with other therapies. There is a high prevalence of symptoms and distress in heat failure (HF) necessitating palliative care, which include not just dyspnoea and oedema but also a range of other symptoms that are all sub-optimally controlled at the end of life. 1 For patients with HF, palliative care attends to physical, psychological, social and spiritual distress, caring for both patients and families with optimisation of quality of life. 2 Palliative care also facilitates communication and complex decision-making with advance care planning. Palliative support should be offered once there is a need. Prognostic indicators are also available in alerting clinicians to timing and need for palliative care, especially in older patients. 3 Evidence for benefit of early palliative care is emerging for structured palliative care services for HF. The PAL-HF randomised controlled trial shows that an interdisciplinary palliative care can yield greater benefits in quality of life, anxiety, depression, and spiritual well-being compared with usual care alone. 4 Challenges in withholding or withdrawing care options like with non-invasive ventilation, implantable defibrillators, left ventricular assistive devices will need to be further addressed. Serious illness conversation guide from Harvard University is available also in local Hong Kong Chinese setting to facilitate discussion. 5 Good HF care necessitates an integrated care programme, with palliative team working hand in hand with cardiologists. References: Gibbs LME, Addington-Hall J, Gibbs JSR. Dying from Heart Failure: lessons from Palliative Care. BMJ 1998;317:961–962. Braun LT, Grady KL, Kutner JS, et al . Palliative Care and Cardiovascular Disease and Stroke: A Policy Statement from the American Heart Association/American Stroke Association. Circulation 2016;134:e198–e225. Coventry PA, Grande GE, Richards TA, Todd CJ. Prediction of appropriate timing of palliative care for older adults with non –malignant life-threatening disease. A systematic review. Age Ageing 2005;34:218–27. Rogers JG, Patel CB, Mentz RJ, et al . Palliative Care in Heart Failure: The PAL-HF Randomised, Controlled Clinical Trial. J Am Coll Cardiol 2017;70:331–341. Jockey Club End-of-Life Community Care Project. Serious illness communication guide in Hong Kong, 2018. (accessible at https://youtu.be/_5RxXYHWCPg).